Rare case of nephrotic syndrome: Schimke syndrome - Pedrosa,Anna Kelly Krislane de Vasconcelos (2016)
Abstract Schimke syndrome corresponds to dysplasia of bone and immunity, associated with progressive renal disease secondary to nephrotic syndrome cortico-resistant, with possible other abnormalities such as hypothyroidism and blond marrow aplasia. It is a rare genetic disorder, with few reports in the literature. The most frequent renal involvement is nephrotic syndrome with focal segmental glomerulosclerosis and progressive renal failure. The objective of this study was to report a case of Schimke syndrome, diagnostic investigation and management of the case.